Etiological treatment of young women infected with Trypanosoma cruzi, and prevention of congenital transmission - Sosa-Estani,Sergio (2009)
The objective was to detect Trypanosoma cruzi infection in 32 children in Salta, Argentina, born to 16 chronically infected young women who were treated with benznidazole. Tests were performed to assess the efficacy of treatment after 14 years. At the end of the follow up, 87.5% of the women were non-reactive to EIA tests, 62.5% to IHA and 43.8% to IFA. 62.5% of the women were non-reactive according to two or three serological tests. No infected children were detected among the newborns of mothers treated before their pregnancy.